Survival Outcomes of Patients With Stage IB3 Cervical Cancer Who Undergo Abdominal Radical Hysterectomy Versus Radiochemotherapy - Li, Zhiqiang; Yang, Qing; Guo, Jianxin; Liang, Guoqiang; Duan, Hui; Wang, Shaoguang; Hao, Min; Liang, Wentong; Li, Donglin; Zhan, Xuemei; Xie, Qinghuang; Lang, Jinghe; et al. (Frontiers in Oncology, 2022)
Objective This study aimed to compare the survival outcomes of abdominal radical hysterectomy (ARH)+pelvic lymphadenectomy±para-aortic lymph node dissection versus radiochemotherapy (R-CT) among stage IB3 cervical cancer patients. Methods Based on the large number of diagnoses and treatments for cervical cancer in the Chinese database, propensity score matching (PSM) was used to compare the 5-year overall survival (OS) and disease-free survival (DFS) rates of the ARH group and R-CT group. Results There were 590 cases of stage IB3 cervical cancer according to the FIGO 2018 staging system, with 470 cases in the ARH group and 120 cases in the R-CT group. The ARH and R-CT groups showed different 5-year OS and DFS rates in the total study population, and the 5-year OS and DFS rates in the R-CT group (n = 120) were lower than those in the RH group (n = 470) (OS: 78.1% vs. 92.1%, p < 0.001; DFS: 71.6% vs. 90.3%, p < 0.001). R-CT was associated with a worse 5-year OS rate (hazard ratio [HR]=3.401; 95% confidence interval [CI]=1.875–6.167; p< 0.001) and DFS rate (HR=3.440; 95% CI=2.075–5.703; p< 0.001) by Cox multivariate analysis. After 1:3 PSM, the 5-year OS and DFS rates in the R-CT group (n = 108) were lower than those in the RH group (n = 280) (OS: 76.4% vs. 94.0%, p < 0.001; DFS: 69.3% vs. 92.6%, p < 0.001, respectively). R-CT was associated with a worse 5-year OS rate (HR=4.071; 95% CI=2.042–8.117; p< 0.001) and DFS rate (HR=4.450; 95% CI=2.441–8.113; p< 0.001) by Cox multivariate analysis. Conclusion Our study found that for FIGO 2018 stage IB3 cervical cancer patients, ARH resulted in better OS and DFS than R-CT.